Aetheapnomyia Harbach & Greenwalt (Diptera: Culicidae: Culicinae: Aedini) revisited based on a new record from Rovno amber - Zakrzewska, Marta; Perkovsky, Evgeny E.; Harbach, Ralph E.; Giłka, Wojciech (Zootaxa, 2025)
The extinct genus Aetheapnomyia Harbach & Greenwalt, 2012 (Diptera: Culicidae) and its type species, At. hoffeinsorum (Szadziewski, 1998), originally described from Baltic amber, are more fully described based on a specimen of the type species recently found in Rovno amber. Dipteran inclusions in Baltic and Rovno ambers are reviewed and the possible affinities of Aetheapnomyia with extant aedine mosquitoes are explored.